Tra percezione e lingua: alcune osservazioni sul funzionamento dei complementi che fanno riferimento alle proprietà fisiche degli esseri umani - Kwapisz-Osadnik, Katarzyna (Studia Romanica Posnaniensia, 2013)
The paper explores a wide variety of complements that in Italian syntax happen to have the same reference. The case in point is their ability to evoke two physical features, e.g. on the one hand, 'to be bald' (to have no hair), 'to have little hair', 'to have lost one’s hair', and on the other, 'to have grey hair', 'to have gone / grown grey', 'to have plenty of grey hair on one’s head', 'to be grey-haired', 'to have hardly any grey hair'. The present remarks start by pointing at the close proximity between a way some particular reality is perceived (involving, with respect to concepts, schemata, preconceptions and imaging) and the form of putting it into words. This proximity explains why in Italian grammars numerous interchangeable complements are applied – the reason for their diversity comes from concurrent perceptions of the same reality.